Analysis of The Physical, Chemical, and Organoleptic Quality of Fried Peas with SPC (Statistical Process Control) And PCA (Principal Component Analysis) Approaches - Risma Novita Sari; Yoyok Budi Pramono; Setya Budi Muhammad Abduh (Jurnal Teknologi Hasil Pertanian, 2024)
The study aims to analyze the consistency of the quality of fried peas with statistical process control aids. Samples were taken daily for 28 days from a nut frying business. The quality of samples including color, free fatty acid, peroxide value, and organoleptic is tested daily with 5 repetitions. Quantitative quality consisting of color, moisture content, free fatty acids, and peroxide value is analyzed with SPC while organoleptic quality is analyzed with PCA. Analysis with SPC results in an upper control limit and a lower control limit of 68.6%; 25;4; 43.7 and 37.7; 8,7; 22.6 for L*, a*, and b*, 2.275% and 2.072% for moisture content, 0.628% and 0.145% for free fatty acids, and 1.075 mEqO2/kg and 0.079 mEqO2/kg for peroxide value. Based on the upper control limit and the lower control limit, pea quality is inconsistent for variable moisture content, free fatty acids, and peroxide value. Analysis of PCA color, moisture content, free fatty acids, peroxide value, and sensory products did not show certain grouping and clustering patterns, which meant the samples were relatively the same as each other. Even though the variables of water content quality, free fatty acids, and peroxide value of fried peas are inconsistent, they are not detected by panelists. The causative factors of quality deviation can be known with certainty by examining each factor listed in the fishbone diagram. In addition, monitoring also needs to be done routinely and closer to the production process to find out exactly the cause of product quality deviations.